Acute renal failure induced by markedly decreased appetite secondary to a depressive episode after discontinuation of long-term lithium therapy in an elderly patient with bipolar disorder. (16th May 2014) - Okada, Akira
Abstract : Some elderly patients on chronic lithium therapy for bipolar disorder and their doctors may be faced with a therapeutic dilemma over whether or not to continue prescribing/taking lithium given their increased risk of reduced renal function. We present the case of a 78-year-old woman with bipolar disorder who discontinued lithium therapy due to increased risk factors for renal injury. After discontinuation, she experienced markedly decreased appetite secondary to a depressive episode, and developed acute renal failure, which subsequently progressed to a more advanced stage of chronic kidney disease. This case suggests that extreme care must be taken to prevent the recurrence of depression in elderly patients with bipolar disorder who discontinue lithium therapy, even when they had been emotionally stable for a long time while receiving lithium. Medications other than lithium for bipolar disorder may be needed at the time lithium therapy is discontinued.